Knowledge of and attitudes towards extending professional powers among departmental nurses with respect to issuing prescriptions and independent referring for diagnostic tests – preliminary report - Zarzeka, Aleksander; Panczyk, Mariusz; Ścieglińska, Bożena; Belowska, Jarosława; Iwanow, Lucyna; Gotlib, Joanna (Polish Journal of Public Health, 2018)
Introduction. An independent prescribing certain drugs, including issuing prescriptions, as well as an entitlement to refer patients for certain diagnostic tests, constitute the key competences of an advanced nurse/midwife practice.Aim. To analyze knowledge and attitudes of departmental nurses (DN) towards extending professional powers of nurses and midwives.Material and methods. The sample involved 23 DN (women: 100%) working in the Independent Public Children’s Teaching Hospital in Warsaw. The mean age was 49 years (mode and median: 50; min. 31, max. 61, SD=7.95). The mean of professional experience was 30 years (mode: 25, median: 30, min. 17, max. 40, SD=6.38). A voluntary and anonymous questionnaire with 10 questions referring to knowledge and 32 statements concerning attitudes evaluated in the Likert scale was conducted.Results. Almost all DN knew that prescribing drugs is a right and not an obligation. Nearly half of the DN knew when the new regulations shall enter into force. DN believed that the new regulations shall improve patient care and increase patient’s comfort and access to services. DN concern about preparation of nurses and midwives for new competences.Conclusions.• The study group’s level of knowledge about the new competences was insufficient and requires supplementing.• The attitudes of the study group towards the new competences were not unambiguous. It should, however, be noted that the study was conducted in a specialized children’s teaching hospital, where the application of the amended regulations is limited.• Although the nursing management staff supports the legislative changes, they object to the process of introducing them. This applies particularly to the necessity of an adequate preparation of nurses and midwives.• The study should be continued among a representative group of nurses with a similar level of education, professional experience, and place of work, with particular consideration of nurses working in the outpatient health care.